1999
DOI: 10.1002/(sici)1097-4644(19990615)73:4<563::aid-jcb14>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Direct effects of prolactin on corticosterone release by zona fasciculata-reticularis cells from male rats

Abstract: The role of prolactin (PRL) in the male is not fully defined. The aim of this study was to investigate the function and mechanism of PRL on the production of corticosterone by zona fasciculata-reticularis (ZFR) cells in vitro. The ZFR cells were obtained from male rats under normal, hyperprolactinemic, or hypoprolactinemic situation. PRL stimulated the corticosterone release in a dose-dependent pattern in the ZFR cells from normal male rats. The cellular adenosine 3'-5'-cyclic monophosphate (cAMP) concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…These results also suggest that hypersecretion of CRH probably occurs in hypoprolactinemia rats. Previous studies have shown that PRL could act directly on adrenal gland to drive corticosterone secretion [2,4,6,[7][8][9][10]. In the present study, PRL stimulated the secretion of corticosterone from cultured adrenal cells in synergy with low levels of ACTH in all rat models.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…These results also suggest that hypersecretion of CRH probably occurs in hypoprolactinemia rats. Previous studies have shown that PRL could act directly on adrenal gland to drive corticosterone secretion [2,4,6,[7][8][9][10]. In the present study, PRL stimulated the secretion of corticosterone from cultured adrenal cells in synergy with low levels of ACTH in all rat models.…”
Section: Discussionsupporting
confidence: 67%
“…Several studies in the literature have examined the role of PRL on adrenal gland function as well as its effects on lactation and reproduction [1][2][3][4][5][6]. Although adrenocorticotropic hormone (ACTH) is generally considered to play a major role in the regulation of adrenocortical secretion, previous reports showed that PRL could act directly on adrenal gland to drive corticosterone secretion [2,4,6,[7][8][9][10]. Additionally, PRL receptors (PRL-R) are expressed in the adrenal cortex in several species [1,7,[11][12][13].…”
mentioning
confidence: 99%
“…Further studies from our own laboratory have shown that these changes in steroid hormone production and secretion are not a function of reduced ACTH receptors, cAMP production, cAMP phosphodiesterase, steroidogenic enzymes or lipoprotein-mediated cholesterol delivery and the major alteration in the respective cell types occurs distal to cAMP generation [297,298,[303][304][305]. In contrast, several reports from one laboratory, however, suggests that the adrenocortical cells isolated from aged female rats in fact possess an enhanced capacity to secrete corticosterone in response to ACTH stimulation than cells from young or adult animals [306][307][308][309][310]. Finally, there is also evidence for age-related impaired aldosterone secretion by the isolated rat adrenal capsules and glomerulosa cells [311,312].…”
Section: Experimental Animalsmentioning
confidence: 99%
“…Furthermore, Chang et al (2002) reported that food deprivation enhances enzyme activity of P450 11beta and elevates plasma corticosterone level. In this study, food intake and body weight gain decreased both in the 4 dayand 4 week-HSD groups, compared to each age-matching control.…”
Section: Et Al 2001mentioning
confidence: 99%
“…The plasma Na + has been suggested to be a physiological stressor breaking the cellular homeostasis (Ogishima et al, 1992) and a stress activation of the hypothalamic-pituitaryadrenal axis elevates plasma corticosterone level via ACTH release. It has been reported that surgical stress and nutritional stress, such as food deprivation, all increase P450 11beta expression in the adrenal cortex in relation with increased plasma glucocorticoids (Engeland et al, 1997;Chang et al, 2002). Therefore, it appears that the extended salt loading, likely as physiological stress, may increase the adrenal expression of P450 11beta by activating the hypothalamicpituitary-adrenal axis.…”
Section: Et Al 2001mentioning
confidence: 99%